Uji Sifat Campuran Bahan Aktif Herbisida Atrazin, Nikosulfuron, Mesotrion pada Pengendalian Beberapa Jenis Gulma - Sembodo, Dad Resiworo Jekti; Wati, Nana Ratna; Susanto, Herry; Sugiatno, Sugiatno (JURNAL AGROTROPIKA, 2024)
The aim of this research was to know effectiveness and characteristic of mixing herbicide active ingredients atrazine, mesotrion, and nikosulfuron on several weed specieses. The trial conducted in the green house at South Lampung from December 2021 until February 2022. This Research arranged in a Randomized Completely Design. Treatment consists of four types of herbicides with six level of dosage active ingredient, namely of single herbicides is atrazin 200 g/l (0, 25, 50, 100, 200, and 400 g ha-1), nikosulfuron 20 g/l (0, 2.5, 5.0, 10, 20, and 40 g ha-1), mesotrion 40 g/l (0, 5, 10, 20, 40 and 80 g ha-1), and herbicides combination of atrazine, nikosulfuron, and mesotrion 200/20/40 OD (0, 32.5, 65, 130, 260, and 520 g ha-1). The target weed were 3 type of broadleaves weeds (Ageratum conyzoides, Euphorbia hirta, and Richardia brasiliensis), 3 type of grasses weeds (Digitaria ciliaris, Eleusine indica, and Rottboellia cochinchinensis), and sedges weed (Cyperus rotundus). Multiplicative Survival Model method used in this research because atrazin, nikosulfuron, and mesotrion have different mode of action. Results showed that an active ingredient mixture of atrazin 200 g/l, nikosulfuron 20 g/l, and mesotrion 40 g/l has LD50 expectation value of 155.96 g ha-1 and LD50 treatment of 74.27 g ha-1 with the co-toxicity value was 2.10 (co-toxicity >1), it means that the characteristic oh the herbiscides mixture  is synergist or not antagonist. Keywords: herbicide mixture, atrazine, mesotrion, nikosulfuron, LD50, Multiplicative Survival Model